The role of the formation of ideological immunity in young people in ensuring information and psychological security (Texas Journal of Multidisciplinary Studies, 2021)
This article highlights the importance of the formation of ideological immunity in young people in ensuring information and psychological security, as well as the study of the growing spiritual needs of students and the formation of their interest and positive attitude to the idea of national independence.